A Challenge: Mental Health Protection Policies for Victims of Gender Based Violence (Universitas Terbuka, 2025)
This study aims to analyze the policy challenges in protecting the mental health of victims of gender-based violence in Indonesia, focusing on stigma, service accessibility, budget pressures, and institutional collaboration. The approach used was a review of legal documents, institutional reports, and scientific publications from the past five years (2019–2024). The results show that although Indonesia has a progressive legal framework, such as the Sexual Violence Crime Law, its implementation still faces significant challenges. Social stigma against victims leads to low reporting rates and reluctance to seek psychological help. Additionally, limited mental health service infrastructure at the primary level, especially at community health centers (Health Centers), restricts victims' access to proper care. Budget constraints in the mental health sector, combined with a lack of coordination between government and non-governmental organizations, worsen gaps in comprehensive protection. This study recommends strengthening related regulations, developing integrated psychosocial services, increasing the capacity of mental health professionals, and launching a national campaign to eliminate stigma against victims of violence. With strategic and collaborative efforts, policies that address the mental health needs of victims of gender-based violence can be effectively implemented.